Work and participation schemes in the recovering enterprises processes in Argentina in the new century - Deux Marzi, Maria Victoria (Universidad Nacional del Litoral, 2020)
In this article we describe and analyze recovering enterprises processes in the period from 2000 to 2017, understood as a processes defined by the confluence of bankruptcy or closure of an existing company and the workers' decision to continue the activity, assuming themselves the management of the economic unit. After more than a decade of the first recovering enterprises processes we are particularly interested in analyze processes that have managed to sustain relatively stable over this period, transposing the foundational and incipient recovery stage. Thus, focusing on the consolidation phase of the process, we asked for the characteristics of the economic forms and social relations that have actually been consolidated in the processes analyzed, and the nature and scope of the transformations in both (forms economic and social relations) have taken place. All this brings us to know if the new settings are a socially different work experience